39.9k views
5 votes
How can csc^2-cot^2 = 1?

User Psicopoo
by
4.8k points

1 Answer

5 votes

ANSWER

By simplifying the left hand side using the Pythagorean Identity.

Step-by-step explanation

The given identity is


\csc^(2) (x) - \cot^(2) (x) = 1

Take the left hand side and simplify to get the right hand side.


\csc^(2) (x) - \cot^(2) (x) = (1)/(\sin^(2) (x)) - ( \cos^(2) (x))/(\sin^(2) (x))

Collect LCM for the denominators.


\csc^(2) (x) - \cot^(2) (x) = (1 - \cos^(2) (x))/(\sin^(2) (x))

Recall the Pythagorean Identity.


\cos^(2) (x) + \sin^(2) (x) = 1

This implies that:


1 - \cos^(2) (x) = \sin^(2) (x)

We substitute this to get,


\csc^(2) (x) - \cot^(2) (x) = (\sin^(2) (x))/(\sin^(2) (x))


\csc^(2) (x) - \cot^(2) (x) = 1

User Sandoz
by
4.9k points